Effect of air nanobubbles on oxygen transfer, oxygen uptake, and diversity of aerobic microbial consortium in activated sludge reactors. (May 2022) - Yaparatne, Sudheera; Doherty, Zachary E.; Magdaleno, Andre L.; Matula, Emily E.; MacRae, Jean D.; Garcia-Segura, Sergi; Apul, Onur G.
Graphical abstract: Highlights: Nanobubble aeration of activated sludge was tested against coarse bubble aeration. Nanobubble aeration showed 6-fold higher oxygen transfer into water. Nanobubbles yielded 10% higher soluble chemical oxygen demand removal. Sludge settleability increased and floc formation was diminished by nanobubbles. The microbiome of the nanobubble aerated sample has lower alpha and beta diversities. Abstract: Nanobubbles have the potential to curtail the loss of oxygen during activated sludge aeration due to their extensive surface areas and lack of buoyance in solution. In this study, nanobubble aeration was explored as a novel approach to enhance aerobic activated sludge treatment and benchmarked against coarse bubble aeration at the lab scale. Nanobubble aerated activated sludge reactors achieved greater dissolved oxygen levels at faster rates. Higher soluble chemical oxygen demand removal by 10% was observed when compared to coarse bubble aeration with the same amount of air. The activated sludge produced compact sludge yielding easier waste sludge for subsequent sludge handling. The samples showed fewer filamentous bacteria with a lower relative abundance of floc forming Corynebacterium, Pseudomonas, and Zoogloea in the sludge. The microbiome of the nanobubble-treated activated sludge showed significant shifts in the abundance of community members at the genus level and significantly lower alpha and beta diversities.